Asymptotic Estimates of the Number of Solutions of Systems of Equations with Partial Boolean Functions - Edward V. Yeghiazaryan (Изд-во НАН РА)
In this paper a class of systems of equations with partial (not everywhere defined) Boolean functions is investigated. The asymptotic estimate of the number of solutions of systems of equations is determined for the "typical" case.
Keywords: Mathematics; Analysis